Rusty World: A Working Paper on Video Games and Social Class - O'Connor, Alan (Loading, 2025)
This working paper provides a preliminary treatment of issues of social class in relation to the video game Rust as it is played on servers and streamed on Twitch. The paper uses the sociology of Pierre Bourdieu to explore Rust as a field and to describe the social class habitus of those who play and stream the game.